Chronic corticosterone administration in adolescence enhances dorsolateral striatum-dependent learning in adulthood - Gadberry, Ty M.; Goodman, Jarid; Packard, Mark G. (Frontiers in Behavioral Neuroscience, 2022)
Previous evidence indicates a link between early life stress (ELS) in humans and a predisposition to psychopathologies that are characterized in part by maladaptive habitual behaviors. Stress and anxiety influence the relative use of mammalian memory systems implicated in these disorders. Specifically, cognitive memory functions of the hippocampus are typically impaired by stress/anxiety, whereas habit memory functions of the dorsolateral striatum (DLS) are enhanced. A stress/anxiety bias towards habit memory has largely been demonstrated in adult rodents and humans, and the effects of ELS on the later use of DLS-dependent habit memory in adult rodents have not been extensively examined. The present study addressed this question by chronically elevating corticosterone (CORT) during adolescence, and investigated the effects of this treatment on DLS-dependent habit learning in adulthood. In experiment 1, adolescent rats received a single daily injection of either CORT (5 mg/kg) or vehicle (VEH) over five days and then matured undisturbed before training as adults in a DLS-dependent water plus-maze task. Rats administered CORT injections during adolescence displayed a strong trend (p= 0.0504), towards enhanced learning during adulthood relative to vehicle-treated rats. Adolescent CORT administration also increased anxiety-like behavior in adulthood in an elevated plus-maze test 48 hours after maze training. In experiment 2, adolescent CORT administration enhanced task acquisition in adulthood, and this effect was blocked by concurrent administration of the glucocorticoid antagonist mifepristone (30 mg/kg). Taken together, these findings suggest that chronic elevation of glucocorticoids during adolescence are sufficient to facilitate habit learning in adulthood, and indicate that glucocorticoid function may be a potential underlying mechanism by which early life stress influences subsequent habitual behaviors.